THE EFFECT OF RETURN ON EQUITY, PRICE EARNING RATIO AND DEBT TO EQUITY RATIO ON RETURN OF SHARES OF FOOD AND BEVERAGES COMPANIES REGISTERED IN INDONESIA STOCK EXCHANGE FOR 2012-2014 - Izzakud Wahasanah; Sengguruh Nilowardono (NAROTAMA UNIVERSITY, Indonesia, 2020)
The presence of the capital market in Indonesia is marked by the number of investors who have started investing in the food and beverage industry. The more rapid development of the food and beverage sector is followed by the increasing demand for public needs, thus making investors need funds from external sources. Funds from external sources can be obtained through the capital market. Therefore, the owner is directed to the capital market which can attract investors. Investors tend to choose stocks that can provide maximum returns. This study aims to determine the effect of return on equity (ROE), price earning ratio (PER), and debt to equity ratio (DER) on stock returns in food and beverage companies listed on the IDX (case study 2012-2014). The analysis technique used in this research is multiple linear regression to obtain a comprehensive picture of the relationship between one variable and another. The explanatory technique used is the multiple linear regression method (F test and T-test) coefficient of determination analysis and correlation coefficient analysis. So it can be concluded that the variable (X) is ROE, PER, and DER and variable (Y) RETURN SHARES. The results of the study show that together the financial performance as measured by ROE, PER, and DER has a significant effect on stock returns in food and beverage companies in the 2012-2014 period. The results of this study are expected that the variables ROE, PER, and DER can be used as a good guideline for the management of the company in improving financial performance, especially capital management, debt, and the ability to generate profits, or by investors in determining investment strategies.